2023
DOI: 10.1038/s41598-023-36105-4
|View full text |Cite
|
Sign up to set email alerts
|

Iron nanoparticle regulate succinate dehydrogenase activity in canola plants under drought stress

Abstract: Application of nutrients as nanoparticle (NP) is an operative manner of nutrient supply for plants, especially under stress conditions. The present study was designed to highlight the role of iron NP on drought tolerance and elucidate the underlying mechanisms in drought-stressed canola plants. Drought stress was imposed by polyethylene glycol different concentrations (0, 10 and 15% (W/V)) with or without iron NP (1.5 and 3 mg/l). A comparative study of several physiological and biochemical parameters have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Moreover, it enhances non-enzymatic antioxidants and employs a cofactor for a large number of enzymes (about 140) [25]. Enhancing vegetative growth and yield components may be caused by the beneficial effects of iron nanoparticles on plant growth and yield contents through increased synthesis of GA3 and jasmonic acid, the formation of chloroplasts, and the strengthening of the sink-source relationship [26]. Additionally, past research has shown that Fe-NPs are essential for directly and indirectly inducing antioxidant mechanisms, detoxifying reactive oxygen species, and maintaining osmotic equilibrium in plants contents [26].…”
Section: Figure 4: Xrd Of Feo Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it enhances non-enzymatic antioxidants and employs a cofactor for a large number of enzymes (about 140) [25]. Enhancing vegetative growth and yield components may be caused by the beneficial effects of iron nanoparticles on plant growth and yield contents through increased synthesis of GA3 and jasmonic acid, the formation of chloroplasts, and the strengthening of the sink-source relationship [26]. Additionally, past research has shown that Fe-NPs are essential for directly and indirectly inducing antioxidant mechanisms, detoxifying reactive oxygen species, and maintaining osmotic equilibrium in plants contents [26].…”
Section: Figure 4: Xrd Of Feo Nanoparticlesmentioning
confidence: 99%
“…Enhancing vegetative growth and yield components may be caused by the beneficial effects of iron nanoparticles on plant growth and yield contents through increased synthesis of GA3 and jasmonic acid, the formation of chloroplasts, and the strengthening of the sink-source relationship [26]. Additionally, past research has shown that Fe-NPs are essential for directly and indirectly inducing antioxidant mechanisms, detoxifying reactive oxygen species, and maintaining osmotic equilibrium in plants contents [26]. In comparison to the control (T1), which placed last, the T8 produced the following results: plant height of 43.12 cm, fresh weight of 30.41g, dry weight of 2.44g, seed weight of 5.09g, and pod weight of 7.39g at an increase rate of (55.56, 82.97, 162.36, 105.24, and 122.59)%, respectively .…”
Section: Figure 4: Xrd Of Feo Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation